Strategi Usaha Meningkatkan Pendapatan UPTD BPSJ dengan Metode Balance Scorecard - Murdiyanti, Dwi Retno; Suryawati, Chriswardani; Purnami, Cahya Tri (MAHESA : Malahayati Health Student Journal, 2025)
ABSTRACT UPTD Balai Pelayanan dan Saintifikasi Jamu (UPTD BPSJ) strives to increase income to maintain its sustainability in the future. Therefore, UPTD BPSJ needs to regulate business strategies to achieve revenue targets. One way to get a business strategy is with the Balance Scorecard. Balance Scorecard is a way for management to achieve goals by analyzing four perspectives including financial perspectives, learning and growth, internal business processes, and customers. This study was conducted to analyze the business strategy of UPTD BPSJ to increase revenue using the Balance Scorecard method. This type of research is qualitative with a case study design. The results of this study are known based on the financial perspective of UPTD BPSJ inefficient in managing the budget. As for the learning perspective, it was obtained information that productivity decreased due to lack of cooperation with the herbal industry, employee competence is lacking in terms of public speaking skills, using computers, introducing services through digital marketing, lack of communication between employees and units. From an internal business perspective, it is known that obstacles to innovation are that officers feel overlapping work, lack of supervision of minimum service standards and working according to standard operating procedures. Based on the customer perspective, information was obtained that customers feel that product prices are relatively expensive, lack of employee skills in conditioning visitors, the location of UPTD BPSJ cannot be accessed by public transportation, Google directions are not specific enough, and the service of the Laboratorium Saintifikasi Jamu unit is considered slow.The conclusion of this study is that UPTD BPSJ needs to optimize assets and employees to introduce UPTD BPSJ services, improve public speaking and digital marketing competencies of employees, improve effective communication, improve supervision of quality management systems and minimum service standards, evaluate service prices, improve collaboration so that access to UPTD BPSJ is easy and fast service. Keywords: Balance Scorecard, Revenue, Strategy, UPTD BPSJ  ABSTRAK UPTD Balai Pelayanan dan Saintifikasi Jamu (UPTD BPSJ) berupaya untuk meningkatkan pendapatan untuk menjaga keberlangsungannya di masa depan. Oleh karenanya UPTD BPSJ perlu mengatur strategi usaha mencapai target pendapatan. Salah satu cara mendapatkan strategi usaha yaitu dengan Balance Scorecard. Balance Scorecard adalah cara manajemen mencapai tujuan dengan menganalisis empat perspektif meliputi perspektif keuangan, pembelajaran dan pertumbuhan, proses bisnis internal, pelanggan. Penelitian ini dilakukan untuk menganalisis strategi usaha UPTD BPSJ meningkatkan pendapatan dengan metode Balance Scorecard. Jenis penelitian ini kualitatif dengan disain studi kasus. Pengumpulan data dengan observasi, wawancara mendalam dan dokumentasi. Hasil penelitian ini diketahui berdasarkan perspektif keuangan UPTD BPSJ kurang efisien mengelola anggaran. Adapun dari perspektif pembelajaran didapatkan informasi produktivitas menurun karena kurangnya kerjasama dengan industri herbal, kompetensi karyawan kurang dalam hal kemampuan public speaking, menggunakan komputer, mengenalkan layanan melalui digital marketing, kurangnya komunikasi antar karyawan dan unit. Dari perspektif bisnis internal diketahui kendala berinovasi yaitu petugas merasa tumpang tindih pekerjaan, kurangnya pengawasan standar pelayanan minimal serta bekerja sesuai standar operasional prosedur. Berdasarkan perspektif pelanggan didapatkan informasi pelanggan merasa harga produk relatif mahal, kurangnya ketrampilan karyawan mengkondisikan pengunjung, lokasi UPTD BPSJ belum bisa diakses dengan kendaraan umum, petunjuk arah google kurang spesifik, pelayanan Laboratorium Saintifikasi Jamu dinilai lambat. Kesimpulan penelitian ini yaitu UPTD BPSJ perlu mengoptimalkan asset dan karyawan untuk mengenalkan layanan UPTD BPSJ, meningkatkan kompetensi public speaking serta digital marketing karyawan, meningkatkan komunikasi efektif, meningkatkan pengawasan sistem manajemen mutu dan standar pelayanan minimal, mengevaluasi harga layanan, meningkatkan kolaborasi agar akses menuju UPTD BPSJ mudah dan cepat pelayanannya.  Kata Kunci: Balance Scorecard, Pendapatan, Strategi, UPTD BPSJ